The physiological response of Populus tremula x alba leaves to the down-regulation of PIP1 aquaporin gene expression under no water stress - Secchi, Francesca; Zwieniecki, Maciej A. (Frontiers in Plant Science, 2013)
In order to study the role of PIP1 aquaporins in leaf water and CO2 transport, several lines of PIP1-deficient transgenic Populus tremula x alba were generated using a reverse genetic approach. These transgenic lines displayed no visible developmental or morphological phenotypes when grown under conditions of no water stress. Major photosynthetic parameters were also not affected by PIP1 down regulation. However, low levels of PIP1 expression resulted in greater leaf hydraulic resistance (an increase of 27%), which effectively implicated PIP1 role in water transport. Additionally, the expression level of PIP1 genes in the various transgenic lines was correlated with reductions in mesophyll conductance to CO2 (gm), suggesting that in poplar, these aquaporins influenced membrane permeability to CO2. Overall, although analysis showed that PIP1 genes contributed to the mass transfer of water and CO2 in poplar leaves, their down-regulation did not dramatically impair the physiological needs of this fast growing tree when cultivated under conditions of no stress.